Time-resolved characteristics of deuteron-beam generated by plasma focus discharge - Lim, Lian Kuang; Yap, Seong Ling; Bradley, D.A. (Public Library of Science, 2018)
The plasma focus device discussed herein is a Z-pinch pulsed-plasma arrangement. In this, the plasma is heated and compressed into a cylindrical column, producing a typical density of > 10 25 particles/m 3 and a temperature of (1–3) × 10 7 o C. The plasma focus has been widely investigated as a radiation source, including as ion-beams, electron-beams and as a source of x-ray and neutron production, providing considerable scope for use in a variety of technological situations. Thus said, the nature of the radiation emission depends on the dynamics of the plasma pinch. In this study of the characteristics of deuteron-beam emission, in terms of energy, fluence and angular distribution were analyzed. The 2.7 kJ plasma focus discharge has been made to operate at a pressure of less than 1 mbar rather than at its more conventional operating pressure of a few mbar. Faraday cup were used to determine deuteron-beam energy and deuteron-beam fluence per shot while CR-39 solid-state nuclear track detectors were employed in studying the angular distribution of deuteron emission. Beam energy and deuteron-beam fluence per shot have been found to be pressure dependent. The largest value of average deuteron energy measured for present conditions was found to be (52 ± 7) keV, while the deuteron-beam fluence per shot was of the order of 10 15 ions/m 2 when operated at a pressure of 0.2 mbar. The deuteron-beam emission is in the forward direction and is observed to be highly anisotropic.